Використання хмарних технологій в вищих навчальних закладах - Шаховська, Наталія; Кісь, Ярослав; Барна, Андрій (Видавництво Львівської політехніки, 2017)
In terms of budget deficit and increase research universities require adequate solutions for financial Managers of their activities. This article reveals the benefits and risks of using cloud technology to provide IT structure of universities. Research methodology is based on the analysis of publications on cloud expertise used in higher education abroad. This article contains suggestions for strategies of using of cloud computing in national universities.
Keywords: хмарні технології; вища освіта; хмарна стратегія